2009
DOI: 10.1242/jcs.046508
|View full text |Cite
|
Sign up to set email alerts
|

Schizosaccharomyces pombe Cds1Chk2 regulates homologous recombination at stalled replication forks through the phosphorylation of recombination protein Rad60

Abstract: The Schizosaccharomyces pombe rad60 gene is essential for cell growth and is involved in repairing DNA double-strand breaks. Rad60 physically interacts with, and is functionally related to, the structural maintenance of chromosomes 5 and 6 protein complex (Smc5/6). Rad60 is phosphorylated in response to hydroxyurea (HU)-induced DNA replication arrest in a Cds1Chk2-dependent manner. Rad60 localizes in nucleus in unchallenged cells, but becomes diffused throughout the cell in response to HU. To understand the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Previous studies showed that Cds1 limits ssDNA accumulation in part by restraining MCM activity while also blocking Mus81-dependent damage and preventing late origin firing (5,14,24,32). Our data are consistent with this: in cds1⌬ cells, we observe increased RPA accumulation that is MCM dependent, together with Mus81-dependent phospho-H2A.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed that Cds1 limits ssDNA accumulation in part by restraining MCM activity while also blocking Mus81-dependent damage and preventing late origin firing (5,14,24,32). Our data are consistent with this: in cds1⌬ cells, we observe increased RPA accumulation that is MCM dependent, together with Mus81-dependent phospho-H2A.…”
Section: Discussionsupporting
confidence: 92%
“…44 Rad60 phosphorylation is also required to regulate HR at stalled replication forks by ensuring the structural maintenance of the protein complex of chromosomes 5 and 6 (Smc5/6). 45 Nrm1, a transcriptional repressor that acts at the G 1 to S phase transition, is phosphorylated by Cds1 in response to DNA replication stress, which leads to the expression of genes important for DNA replication and repair. 46 Cdc25, a well known Cds1 target, is also phosphorylated by Mek1, which also regulates the nuclear localization of Cdc25 and cell cycle arrest.…”
Section: Methodsmentioning
confidence: 99%
“…However, the modest sensitivity caused by cds1Δ indicated a role for the replication checkpoint during treatment. Cds1 is particularly important for replication fork stalling and restart (e.g., Lindsay et al 1998;Kim and Huberman 2001;Miyabe et al 2009). The homologous recombination protein Rad52 forms nuclear foci in response to a variety of lesions, including double-strand breaks and collapsed or restarting replication forks (Meister et al 2005;Bailis et al 2008).…”
Section: Loss Of the Replication Checkpoint Influences Damage Responsementioning
confidence: 99%